Global education movement: English as a second language teachers’ perceptions of integrating volatility, uncertainty, complexity, and ambiguity elements in lessons - Yaccob, Nur Syafiqah; Yunus, Melor Md; John, Dexter Sigan (Frontiers in Psychology, 2023)
Education evolves and progresses globally in a technology-driven world, highlighting the integration of VUCA elements of volatility, uncertainty, complexity, and ambiguity in lessons. Learners are molded to equip themselves with the world and real-life knowledge in their readiness to adapt to the VUCA world. Global education consists of preparing learners for the VUCA world. This study aimed to investigate the current English as a Second Language (ESL) teaching practices and the ESL teachers’ incorporation of VUCA elements in ESL lessons. This study was conducted quantitatively using a survey questionnaire. This study was administered to 30 ESL teachers from different secondary schools in a district in Malacca. The results from the questionnaire revealed that the ESL participants had positive perceptions toward the adaptation of VUCA in the current ESL lessons. Most of the ESL teachers agreed that they adapted VUCA elements into the activities during lessons, although some showed uncertainty about their knowledge and understanding of VUCA. From the high agreement levels in the findings, it can be concluded that the ESL teachers agreed that VUCA elements through problem-based, digital-based, collaborative, and challenging activities in English lessons are beneficial to assist students’ meaningful and autonomous learning. Based on these findings, implications were made for enhancing ESL teachers’ knowledge, understanding, and skills in adapting VUCA in lessons in response to global education demand.